Polaritons de exciton em super-redes semicondutoras - Medeiros, Fábio Ferreira de (2004)
In this work we study the spectrum (bulk and surface modes) of exciton-polaritons in infinite and semi-infinite binary superlattices (such as, ···ABABA···), where the semiconductor medium (A), whose dielectric function depends on the frequency and the wavevector, alternating with a standard dielectric medium B. Here the medium A will be modeled by a nitride III-V semiconductor whose main characteristic is a wide-direct energy gap Eg. In particular, we consider the numerical values of gallium nitride (GaN) with a crystal structure wurtzite type. The transfer-matrix formalism is used to find the exciton-polariton dispersion relation. The results are obtained for both s (TE mode: transverse electric) and p (TM mode: transverse magnetic) polarizations, using three diferent kind of additional boundary conditions (ABC1, 2 e 3) besides the standard Maxwell's boundary conditions. Moreover, we investigate the behavior of the exciton-polariton modes for diferent ratios of the thickness of the two alternating materials forming the superlattice. The spectrums shows a confinement of the exciton-polariton modes due to the geometry of the superlattice. The method of Attenuated Total Reflection (ATR) and Raman scattering are the most adequate for probing this excitations